Evaluating the Students Perception of Academic Learning Environments in AL-Kindy Collage of Medicine - Habib, uda Adnan (AL-Kindy College Medical Journal, 2016)
Background: Educational environment is one of the most important determinants of an effective curriculum. Students’ perceptions of their educational environment have a significant impact on their behavior and academic progress. Objective: 1. To identify students’ perception to the educational environment.2. To identify any gender or class level differences in the students’ perception.Type of the study: This is a descriptive cross-sectional studyMethodology: The study was carried out on convenient sample of 150 students of 2nd and 5th grade. This study was done in Al Kindy Medical College, Baghdad, Iraq and conducted during the period from the 1st of October 2013 till the end of March 2014, by using DREEM questionnaire a validated universal diagnostic inventory for assessing the quality of educational environment through direct interview. Inclusion criteria include any student from the 2nd and 5th class who agree to participate in the study. The data was entered into a Microsoft Excel spreadsheet and were analyzed using SPSS version 16. Student t test was done to find out the difference between the mean scores, P<0.05 was considered as statistically significant.Results: For all students (n= 150) the total DREEM score of a maximum possible of 200 was 110.18 , it was more positive than negative overall domain score, which means that the students had positive perception and more positive scores than negative. Total DREEM scores were significantly higher for females (M = 138.8; SD = 17.2) than males (M = 132.3; SD = 20.7), although all domains mean scores were higher for female than male, there was statistical significant difference regarding Students’ perception of learning, Students’ perception of atmosphere and Students’ social self-perception.Regarding the class level, 5th year students gave significantly higher total DREEM ratings (M = 139.1; SD = 17.4) than 2nd year students (M = 135; SD = 18.8). Second year students also gave significantly higher Students’ perception of learning (SPL) ratings than 5th year students and significantly higher Students’ perception of atmosphere ( SPA ) ratings higher than 5th year students. Conclusions: Students assessed the educational environment as more positive than negative;. The greatest difficulty was with ‘students’ perception of learning’.